Removal of Methylene Blue and Methyl Red from Aqueous Solutions Using Activated Carbons Obtained by Chemical Activation of Caraway Seed - Dorota Paluch; Aleksandra Bazan-Wozniak; Agnieszka Nosal-Wiercińska; Robert Pietrzak (Molecules, 2023)
In this study, activated carbons were produced through the chemical activation of caraway seeds using three different activators: Na2CO3, K2CO3, and H3PO4. A 1:2 weight ratio of precursor to activator was maintained in every instance. Comprehensive analyses were conducted on the resultant activated carbons, including elemental analysis, textural parameters determination, Boehm titration for surface oxygen functional groups, pH assessment of aqueous extracts, and quantification of ash content. The produced materials were subjected to adsorption tests for methylene blue and methyl red sodium salt from the liquid phase and the effects of adsorbent dosage, pH of the aqueous dye solution, process temperature, and adsorbent–adsorbate contact time on sorption capacity obtained. To characterize the adsorption model of the examined pollutants, both the Langmuir and Freundlich equations were employed. In addition, the sorption capacity of the obtained carbon materials against an iodine aqueous solution was assessed. The specific surface area of the obtained adsorbents ranged from 269 to 926 m2/g. By employing potassium carbonate to chemically activate the starting substance, the resulting activated carbons show the highest level of specific surface area development and the greatest sorption capacity against the tested impurities—296 mg/g for methylene blue and 208 mg/g for methyl red sodium salt. The adsorption rate for both dyes was determined to align with a pseudo-second-order kinetic model. The experimental adsorption data for methylene blue were well-described by the Langmuir model, whereas the Freundlich model was found to be congruent with the data pertaining to methyl red sodium salt.